Cover Feature: Lignin Depolymerization: A Comparison of Methods to Analyze Monomers and Oligomers (ChemSusChem 17/2020). Issue 17 (10th August 2020) - Bartolomei, Erika; Le Brech, Yann; Dufour, Anthony; Carre, Vincent; Aubriet, Frederic; Terrell, Evan; Garcia‐Perez, Manuel; Arnoux, Philippe
Abstract : The Cover Feature shows how complex molecules produced by lignin depolymerization can be analyzed quickly by UV fluorescence. The UV beam excites the molecules present in the liquid solution. The molecules are directly analyzed based on their fluorescence pattern. This method allows screening monomers and oligomers distribution as a function of depolymerization conditions. More information can be found in the Full Paper by E. Bartolomei et al .